2021
DOI: 10.36469/001c.24620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chorea on Self-care Activity, Employment, and Health-care Resource Use in Patients with Huntington’s Disease

Abstract: Background: Chorea is recognized as a prototypic motor feature of Huntington’s disease (HD), but its effect on health-related quality of life (HRQoL) has not been fully explored. This study describes the impact of chorea on HRQoL in patients with HD. Objective: To determine the impact of HD-related chorea on employment, self-care activities, activities of daily living, and health-care resource utilization (HCRU). Methods: Data were drawn from the Adelp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(1 reference statement)
0
1
0
1
Order By: Relevance
“…Regarding productivity, the participants mentioned difficulties in house management, specifically when cooking. Other authors have studied the impact of chorea on productivity, concluding that one of the most common problems experienced by HD patients is difficulties in cooking or preparing meals (Claassen et al, 2021). A study that compared the performance of people with mild PD and HD using a virtual reality tool that simulated a kitchen concluded that all participants had significant difficulties in timely completing tasks in which executive functions were required.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding productivity, the participants mentioned difficulties in house management, specifically when cooking. Other authors have studied the impact of chorea on productivity, concluding that one of the most common problems experienced by HD patients is difficulties in cooking or preparing meals (Claassen et al, 2021). A study that compared the performance of people with mild PD and HD using a virtual reality tool that simulated a kitchen concluded that all participants had significant difficulties in timely completing tasks in which executive functions were required.…”
Section: Discussionmentioning
confidence: 99%
“…Nuestros resultados concuerdan con el estudio de Claassen et al (209) en el que estudiaron el impacto que tenía la corea en el área de la Productividad. Concluyeron que una de las mayores dificultades percibidas era en la cocina y en concreto, en la preparación de alimentos.…”
Section: Discussionunclassified